2013
DOI: 10.1007/s10086-013-1326-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a new natural adhesive composed of citric acid and sucrose for particleboard

Abstract: The development of a natural adhesive composed of materials derived from non-fossil resources is a very important issue. In this study, only citric acid and sucrose were used as adhesive materials for particleboard. A water solution in which citric acid and sucrose were dissolved was used as an adhesive, and the manufacture of particleboard with a target density of 0.8g/cm 3 was attempted under a press condition of 200˚C for 10 min. The optimum mixture ratio of citric acid and sucrose and the optimum resin con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 15 publications
1
78
0
9
Order By: Relevance
“…This is supposedly due to the ester-linked bonds that were formed. Umemura et al (2013) also deduced the same results for particleboard made from softwood.…”
Section: Physical Propertiessupporting
confidence: 64%
See 4 more Smart Citations
“…This is supposedly due to the ester-linked bonds that were formed. Umemura et al (2013) also deduced the same results for particleboard made from softwood.…”
Section: Physical Propertiessupporting
confidence: 64%
“…It seemed that carboxyl groups from citric acid reacted well with hydroxyl groups from teak wood to form ester linked groups, providing strong bonding properties. Umemura et al (2013) found different results, where the optimal properties of softwood particleboard were obtained at a citric acid/sucrose ratio of 25/75. The water resistance of the particleboards is shown in Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 95%
See 3 more Smart Citations